(untitled) (UUM Journal of Legal Studies, 2024)
Agriculture is crucial in guaranteeing food security all over the world. Essentially, farmers play a significant role in food security. Producing improved crop varieties is one of the ways to increase sustainable crop productivity. Farmers in Malaysia, in particular small-scale farmers, are still practicing and relying on some traditional agricultural practices. In order to protect new varieties of crops and plants, there exists some legislation vis-a-vis intellectual property rights (IPRs) in the field of agriculture. Patents and plant breeders’ rights, for instance, bring with them some legal implications towards farmers. This paper aims to examine the existing legislation governing farmer rights in Malaysia, focusing on the relevant provisions of the Protection of New Plant Variety Act 2004 (PNPVA). The research also dwells on current issues pertaining to PNPVA’s implementation and the ongoing proposed amendment. The research has employed doctrinal analysis in its investigation and analysis, which has been based on the available data and materials, supported with input collected from an interview with the Department of Agriculture (DOA). The study has found that the concept of farmer rights should not be jeopardized amidst the Government’s commitment in harmonizing the law with the International Convention for the Protection of New Varieties of Plants (UPOV), while optimizing the access of Malaysian farmers to new crop varieties and plant technologies. The present study has also come to the conclusion that the Government must balance the protection afforded to plant breeders with that granted to the local farming community in Malaysia.